Preparation, characterization, and curing kinetics of elevated and cryogenic temperature-resistant epoxy resin composites - Chengwei Bao; Yanen Wang; Ray Tahir Mushtaq; Kun Zhang; Xinpei Li; Xiaohu Chen (Polymer Testing, 2022)
The elevated-and-cryogenic temperature resisting composites were prepared using tetrafunctional (AG-80) and bifunctional (E-42) epoxy resin blend as the matrix, polyetheramine (D400), and m-xylylene diamine (MXDA) as hybrid curing agents, silane coupling agent (KH-560) as a toughening agent, and micron-sized silicon oxide particles as fillers. The curing kinetics of the composites was investigated by differential scanning calorimetry (DSC), the effect of reaction temperature on the resin system's viscosity, the variation of gel time with temperature, and the heat resistance of the resin system were tested by thermogravimetric analysis. The apparent activation energy and reaction level of the curing reaction was calculated, the curing process was developed, and the elevated and cryogenic mechanical properties set at different times were tested. The results showed that the resin system's viscosity decreased with increasing temperature, 40 °C was determined as the optimum operating temperature, and the heat resistance of the composite was good. The gel time test developed a strategy of pre-curing by vacuum at 40 °C and curing at 60 °C. The compressive strength of the resin system was 99.55 MPa and 159.12 MPa after placing at −196 °C and 160 °C for 4 h, respectively. This study presents a theoretical basis for the curing process and optimization of curing parameters for elevated and cryogenic resistant modified epoxy resin composite and provides a potential application for its future in-situ utilization in deep space exploration and lunar construction.